PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KEJELASAN TUJUAN ANGGARAN, DAN EVALUASI ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH KABUPATEN INDRAGIRI HILIR - M. Azmi Insan Cemerlang; Ria Nelly Sari; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examine the effect of budget participation, budget goal clarity and budget evaluation of the performance of government officials indragiri hilir district. The population in this study is government officials at 34 SKPD in indragiri hilir district.The sampling technique using survey method. The data of this research using primary data directly through a questionnaires and analyzed using SPSS 20.0. The data were analyzed to test the hypothesis using multiple linear regression analsys approach.The result of this study showed that budget participatipation, budget goal clarity and budget evaluation have effect on the performance of govermence officials Indragiri hilir district.Keywords: budget participation,budget goal clarity, budget evaluation and performance of govermance officials.